2018
DOI: 10.1016/j.apenergy.2018.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Towards a comprehensive model for characterising and assessing thermoelectric modules by impedance spectroscopy

Abstract: Thermoelectric devices have potential energy conversion applications ranging from space exploration through to mass-market products. Standardised, accurate and repeatable high-throughput measurement of their properties is a key enabling technology. Impedance spectroscopy has shown promise as a tool to parametrically characterise thermoelectric modules with one simple measurement. However, previously published models which attempt to characterise fundamental properties of a thermoelectric module have been found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…6 Impedance spectroscopy has recently attracted attention as a suitable alternative method for the characterization of TE materials and devices. [8][9][10][11][12][13] This technique, in contrast to the Harman method, measures a wide range of frequencies and not only ac and dc conditions. However, it has similarities with the Harman method, in the sense that ZT can be directly obtained from the high frequency and low frequency limits of the impedance spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Impedance spectroscopy has recently attracted attention as a suitable alternative method for the characterization of TE materials and devices. [8][9][10][11][12][13] This technique, in contrast to the Harman method, measures a wide range of frequencies and not only ac and dc conditions. However, it has similarities with the Harman method, in the sense that ZT can be directly obtained from the high frequency and low frequency limits of the impedance spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The impedance method also requires similar experimental conditions to determine ZT accurately, and can be affected by the Joule effect, 12 and convection and radiation losses as well. 13,14 Here, we have evaluated the effect on the accuracy of both Harman and impedance methods of several experimental conditions, which have not been clearly identified previously. This investigation has been performed employing a skutterudite sample, whose TE properties were previously determined by established commercial instruments.…”
Section: Introductionmentioning
confidence: 99%
“…A number of generations and variations of bismuth telluride based thermoelectric converters or generators (TEGs) have been produced for the RTG system (Mesalam et al 2018Williams et al 2014). Americium-based nuclear power systems have lower power densities and occupy larger volumes for equivalent power outputs than Pu-based systems and offer the option of targeting lower operational temperatures Barco et al 2019a).…”
Section: Thermoelectric Converters For Rtgsmentioning
confidence: 99%
“…An impedance spectroscopy technique that has been developed at Leicester by Mesalam et al (2018) for the rapid evaluation of modules has been reported in detail in Mesalam et al (2018. This method enables rapid diagnosis and isolation of material or manufacturing effects on module properties and performance.…”
Section: Thermoelectric Converters For Rtgsmentioning
confidence: 99%
“…The current excitation is given by Eq. (15) which is equivalent to the current density given in Eq. (2).…”
Section: Quasi Static Response With Temperature Dependent Propertiesmentioning
confidence: 99%